MODERN APPROACHES TO THE TREATMENT OF HEPATIC METASTASES FROM NEUROENDOCRINE TUMORS (LITERATURE REVIEW) - O. V. Chistyakova; O. N. Solovyeva; D. Xiaodong; V. Yu. Kosyrev (Сеченовский вестник)
Originating from cells of the diffuse neuroendocrine system, neuroendocrine tumors are able to produce biogenic amines and peptide hormones. Due to the significantly different list of biologically active compounds and level of activity of secretory cells in tumor tissues, their clinical manifestations varies. Liver is one of the most frequent targeted organs for metastasizing this type of tumors, regardless of localization. After the patients being diagnosed, all the treatment measures are focused on two aspects. The first is to suppress the clinical symptoms and improve the living quality. The second one, an increase in life expectancy. Among all the potentially effectible treatments, surgical resection is the only one that may radically kill the disease. However, its application are limited in some cases. In this regard, in the strategy of therapeutic approaches of neuroendocrine tumors with metastases in the liver, a combination of medical, surgical and renal surgical methods comes to the fore.